FEATURES OF COMPOSITION OF BASIC ROCKS OF KOROSTEN’ COMPLEX AND ORIGIN OF NATIVE TITANIC ORES - Galetsky, L.; Comsky, M.; Remezova, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the paper the geochemical peculiarities of titanium-bearing massifs of gabbroidic rocks of Korosten’ pluton were analyzed. On a basis of statistic data handling of chemical analyses of rocks and minerals the calculations of normative mineral composition were made; the formulae of factorial load of two factors connected with processes of ilmenite concentration in the varietes of rocks of gabbro-anortozitic formation were found. Because of received data analysis, the conclution concerning two ways of primary titanium ore- forming procrsses depending from hydrodynamical conditions in the poral space of generated gabbroidic massifs was made.